A new surgical procedure for synchronous esophageal squamous cell carcinoma and gastric adenocarcinoma: Case report. Issue 9 (March 2019) - Zhao, Yunpeng; Cong, Bo
Abstract: Rationale: The stomach is always used to reconstruct the upper digestive tract for esophageal cancer operation. However, problems arise when the esophageal cancer and gastric cancer present at the same time. No medical literature mentioned about this surgical procedure till now. Patient concerns: Majority of the patients had the sensation of obstruction when swallowing because of the esophageal tumor. Gastric adenocarcinoma was found when gastroscopy was performed. Diagnosis: Synchronous esophageal squamous cell carcinoma and gastric adenocarcinoma were confirmed by biopsy pathology. Interventions: We describe the new technique as: distal gastrectomy preserving the gastroepiploic vessels, Roux-en-Y gastrojejunostomy and thoracoscopic Ivor Lewis esophagectomy with chest anastomosis. Outcomes: Three patients accepted the surgery and recovered well without any complications. The patients did not undergo any postoperative adjuvant therapy and was doing well without any recurrence till date (23 months, 12 months, 6 months separately). Lessons: This procedure was less invasive and easier to perform for synchronous early-stage gastric cardiac cancer and middle or lower third thoracic esophageal cancer. We recommend the indication as: esophageal tumor was located at least 27 cm away from the incisor teeth (for R0 resection during chest anastomosis, be sure no superior mediastinal lymph nodes metastasis were found preoperation), gastric tumor was located in the distal portion of the gastric tube and evaluated for clinical stage IA.